Physical risk associated with vibration at cycling. (1st September 2014) - Munera, Marcela; Chiementin, Xavier; Crequy, Samuel; Bertucci, William
<x content-type="archive" xml:space="preserve">Abstract</x> The vibrations undergone by men are a well-known and widely studied risk factor in the industrial world. They are transmitted to the whole body or the upper limbs and they are measured, and limited, according to international standards. Disorders resulting from exposure to vibration are varied in nature: osteoarticular, muscular, vascular, and neurological. In this context, an European Directive 2002/44/EC to the protection of workers exposed to vibration, precises thresholds for vibration exposures and defines the procedure for risk prevention. Nevertheless, the effect of vibration is little studied in sports despite the ubiquity of these. Vibration can induce discomfort, degrading performance or causing musculoskeletal disorders. This paper makes an overview of the studies involving the vibrations during cycling. At first, this paper will summarize the different standards and guidelines relating vibration in humans, which present a guide for the measurement and evaluation of the vibration and exposure limits. Secondly, this paper presents a state of the art vibration effects: (i) the physiological and pathological disorders in athletes, (ii) and the performance. A third part will be devoted to the synthesis of numerical studies that represent the biodynamic response and help to predict the effects of human body vibration. Finally, new research and innovations will be discussed based on studies in other sports.